PSYCHOLOGICAL FIRST AID FOR ADOLESCENCE VICTIM OF BULLYING - Nugrahanto, Albertus Ardana (Journal of Psychiatry Psychology and Behavioral Research, 2025)
Introduction – One of the most common forms of physical and emotional violence found in children and adolescents is bullying. Bullying is a global problem that can be a serious threat to the physical and emotional health of children and adolescents. PFA is the first line of psychological support that can be given to people who are experiencing a crisis, including victims of bullying. It is hoped that this knowledge related to PFA can be a solution in helping to overcome the problem of bullying in adolescents. Methods – Researchers employed the literature review method in this study, collecting different literature from 2011 to 2021 that explores bullying, psychological first aid, and psychological first aid for adolescent victims of bullying. Results – Trauma from bullying has been reported to be associated with chronic and severe psychiatric pathology, including mood and anxiety disorders, post-traumatic stress disorder (PTSD), alcohol and drug abuse, and personality disorders. In addition, the most feared consequence to bullying is its significant association with suicidal tendencies. Discuss – The PFA training or orientation takes place throughout between a half or a full day course, and explains the basic concepts and principles of PFA, such as how to approach situations safely, how to support very distressed people, and how not to cause further harm. PFA training uses participatory learning methods such as role playing Conclusion – Psychological first aid is one of the protections that can be provided with the aim of helping the victim to recover after the bullying incident. PFA can be carried out by non-mental health professionals, parents, and school personnel, especially teachers and/or school nurses, therefore, they are expected to take part in PFA training.